2020
DOI: 10.1080/00173134.2019.1701704
|View full text |Cite
|
Sign up to set email alerts
|

Low taxonomic resolution of papillate Cupressaceae pollen (former Taxodiaceae) impairs their applicability for palaeo-habitat reconstruction

Abstract: Supplementary Figure S1. Schematic drawings of papillate pollen to illustrate hydration levels, papilla configuration, hiatus development, and measurements of morphological characters. A1-4. Stages of hydration (redrawn after VanCampo 1951). A1. Fully hydrated pollen in EV. A2-3. Stages of desiccation. A4. Fully dehydrated pollen. B1-4. Stages of radial splitting, pollen PV (redrawn after VanCampo 1951). C1-6. Papilla configuration in EV. C1. Papilla straight. C2-3. Papilla weakly bent. C4. Papilla sharply ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 45 publications
0
4
1
Order By: Relevance
“…Erdtman et al (1961) described that exine is 1.5 μm thick in J. communis . Khan et al (2018) reported exine thickness ranges 0.4, 0.4, and 0.25 μm for the J. communis , J. excelsa , and J. squamata , respectively, and these result differ from the present finding (Bouchal & Denk, 2020; Galveias et al, 2021).…”
Section: Discussioncontrasting
confidence: 92%
“…Erdtman et al (1961) described that exine is 1.5 μm thick in J. communis . Khan et al (2018) reported exine thickness ranges 0.4, 0.4, and 0.25 μm for the J. communis , J. excelsa , and J. squamata , respectively, and these result differ from the present finding (Bouchal & Denk, 2020; Galveias et al, 2021).…”
Section: Discussioncontrasting
confidence: 92%
“…The origin of both shoots and cones from the same "whole-plant" is supported by the respective morphological correspondence to the same parts of fossil specimens described by Kvaček (1989) R e m a r k s . Pollen grains generally are well preserved but difficult to recognize at the genus or species level in the absence of SEM analyses (Hernandéz-Castillo et al 2005, Sokolova et al 2017, Bouchal and Denk 2020. In this study, only Taxodium/Glyptostrobus-type (Pl.…”
Section: Genus Tetraclinis Mast 1892mentioning
confidence: 74%
“…Based on pollen abundances (electronic supplementary material, table S4), local (close to the lake), regional (occurring in the FPS) and extra-regional ( potentially occurring outside the FPS) vegetation can be inferred. Local vegetation consisted of BLD forests subjected to flooding (Alnus) and NLD swamp forests ( papillate Cupressaceae; [66]). Close to the lake, a mixed forest with Fagus, Abies and Cathaya thrived (using the modern Abant Gölü of northern Turkey as a reference for pollen rain vegetation relationships; [67]).…”
Section: Pollen and Spores: Diversity And Environmental Signalmentioning
confidence: 99%